Clinical entity of cytomegalovirus disease in patients with malignant lymphoma on bendamustine therapy: a single-institution experience. Issue 1 (2nd January 2023) - Iriyama, Noriyoshi; Miura, Katsuhiro; Takahashi, Hiromichi; Nakagawa, Masaru; Iizuka, Kazuhide; Hamada, Takashi; Koike, Takashi; Kurihara, Kazuya; Endo, Toshihide; Nakayama, Tomohiro; Hatta, Yoshihiro; Nakamura, Hideki
Abstract: We investigated the incidence, risk factors, and clinical outcomes of cytomegalovirus (CMV) disease in patients with B-cell lymphoma treated with a bendamustine-containing regimen. The incidence of CMV disease was analyzed after starting treatment with 139 regimens in 126 patients. Clinically significant CMV disease was observed in seven patients. The median duration between bendamustine initiation and the diagnosis of CMV disease was 69 d (range, 40–233), and the median of cycles completed at onset was 2 (range, 1–6). Furthermore, the incidence of CMV disease was significantly higher in the elderly patients than that in the younger patients. The target organs of CMV disease were the liver, gastrointestinal tract, lungs, and retinas. Antiviral therapy was administered to all patients. However, the recurrence of CMV disease was observed in two patients. This study provides information that could contribute to clinicians' decision-making on lymphoma therapy using bendamustine.